2020
DOI: 10.1021/acs.jpcc.0c01083
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Lithiation under Fast Charging Conditions: Atomistic Modeling Insights

Abstract: The charging of lithium ion batteries in a fast and safe manner is critical for promoting the mass adoption of electric vehicles. Li intercalation in graphite electrodes is known to be one of the bottlenecks during the fast charging process. The mechanism of Li diffusion in highly polarized graphite anode at high current rates remains, however, not well understood. Herein, Density Functional Theory (DFT) calculations are used to gain insights into the Li diffusion process in graphite when it is far from equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…[113,151,177,[232][233][234][235][236] For LIBs, the graphite anode hinders high-rate charge and discharge, limiting the development of electric vehicles and fast-charging consumer technologies. [237,238] Computational studies may screen and predict candidate systems and materials design theories to reduce charging times by calculating migration and diffusion barriers.…”
Section: Metal Migration and Diffusionmentioning
confidence: 99%
See 2 more Smart Citations
“…[113,151,177,[232][233][234][235][236] For LIBs, the graphite anode hinders high-rate charge and discharge, limiting the development of electric vehicles and fast-charging consumer technologies. [237,238] Computational studies may screen and predict candidate systems and materials design theories to reduce charging times by calculating migration and diffusion barriers.…”
Section: Metal Migration and Diffusionmentioning
confidence: 99%
“…The Li migration barrier in graphite (LiC 72 ) is similar (0.34 eV from DFT simulations with D3-BJ corrections) to that of a Li ion on graphene, and has been shown to decrease (indicating more rapid diffusion) with expanding interlayer distance. [142,238] In fully lithiated, sodiated, or potassiated graphite, metal diffusion could also occur through metal vacancy migration (Figure 6). [231,238,244] Through NEB calculations (Figure 6c), a curved migration path was established for LiC 6 and NaC 6 , whereas a straight migration path was found to have the lowest migration activation energy (Figure 6e) for NaC 8 and KC 8 .…”
Section: Metal Migration and Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of experimental and modeling-based techniques have been employed in order to tie the capacity fade of the cells to the local and global degradation mechanisms (via LLI and LAM), such as optical methods, [6] SEM, [28] X-ray diffraction, [16,17,132,189] titration, [25] dV/dQ analysis, [19] Raman spectroscopy, [23] and atomistic modeling. [190] Such studies reveal that irreversible Li plating due to Li concentration gradients across the anode or the electrolyte, [191] electrolyte wetting, and pressure heterogeneity across the anode are the major cause of irreversible capacity loss, with LAM on either electrode usually being a secondary cause, especially with thinner (<100 mm) electrodes. Using such local and global insights into where the Li is lost locally, why it is lost in those regions, and how much Li is lost globally over the entire cell in turn helps improve the battery design and chemistry for optimal XFC behavior.…”
Section: Reducing Recharging Time: Extreme Fast Chargingmentioning
confidence: 99%
“…Graphite, as a common anode material for lithium-ion batteries, will be intercalated with Li + to form the intercalation compound LiC x during the charge–discharge process, and its theoretical specific capacity is as high as 372 mAh g –1 . In fact, it is found that when the voltage exceeds 4.3 V during the charging process, the cathode is highly polarized and anions will also be embedded into the positive graphite to form the intercalation compound MC x (M is a common anion, such as FSI – , PF 6 – , BF 4 – , etc.) to provide a certain level of capacity. On the other hand, Li + gains of electrons in the negative electrode are electroplated, intercalated, or alloyed.…”
Section: Introductionmentioning
confidence: 99%